The Role Of Corporate Governance And Tax Risk In Indonesia Investor Response To Tax Avoidance And Tax Aggressiveness - Amrie Firmansyah; Wahyudi Febrian; Teza Deasvery Falbo (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study examines the effect of tax avoidance and tax aggressiveness on firm value. Besides, this study also analyzes the moderating role of tax risk and corporate governance in this relationship. This study employs secondary data from financial reports and stock price information at www.idnfinancials.com and www.yahoo.finance.com. The sample utilized in this study is Indonesian manufacturing companies from 2016 to 2019. Using purposive sampling, the sample obtained in the study is 260 observations. Data were analyzed employing multiple linear regression for panel data. This study suggests that tax avoidance is positively associated with firm value, while tax aggressiveness is negatively associated. Also, tax risk and corporate governance can reduce the positive effect of tax avoidance on firm value. Furthermore, tax risk and corporate governance can reduce the negative impact of tax aggressiveness on firm value. This study indicates that investors need to pay attention to companies' information to the public. Besides, the Financial Services Authority needs to improve governance policies for companies listed on the Exchange to support Indonesia's investors' protection.